Aerosol–meteorology feedback diminishes the transboundary transport of black carbon into the Tibetan Plateau - Y. Hu; H. Yu; S. Kang; S. Kang; J. Yang; M. Rai; X. Yin; X. Chen; P. Chen (Atmospheric Chemistry and Physics, 2024)
Black carbon (BC) exerts potential effects on climate, especially in the Tibetan Plateau (TP), where the cryosphere and environment are very sensitive to climate change. The TP saw a record-breaking aerosol pollution event during the period from 20 April to 10 May 2016. This paper investigates the meteorological causes of the severe aerosol pollution event, the transboundary transport flux of BC, the aerosol–meteorology feedback, and its effect on the transboundary transport flux of BC during the severe aerosol pollution event using observational and reanalysis datasets as well as simulation based on a coupled meteorology and aerosol/chemistry model, Weather Research and Forecasting model coupled with Chemistry (WRF-Chem). By analyzing weather maps derived from the reanalysis dataset, it is found that the plateau vortex and southerly winds were key factors that contributed to the severe aerosol pollution event. Subsequently, due to the good performance of the WRF-Chem model for the spatiotemporal characteristics of meteorological conditions and aerosols, the transboundary transport flux of BC during the pollution event was investigated. The results show that the vertically integrated cross-Himalayan transport flux of BC decreases from west to east, with the largest transport flux of 20.8 mg m−2 s−1 occurring at the deepest mountain valley in southwestern TP. Results from simulations with and without aerosol–meteorology feedback show that aerosols induce significant changes in meteorological conditions in the southern TP and the Indo-Gangetic Plain (IGP), with the atmospheric stratification being more stable and the planetary boundary layer height decreasing in both regions, and the 10 m wind speed increasing in the southern TP but decreasing in the IGP. Changes in meteorological conditions in turn lead to a decrease in the surface BC concentration in the southern TP of up to 0.16 µg m−3 (50 %) and an increase in the surface BC concentration in the IGP of up to 2.2 µg m−3 (75 %). In addition, it is found that the aerosol–meteorology feedback decreases the vertically integrated transboundary transport flux of BC from the central and western Himalayas towards the TP. This study not only provides crucial policy implications for mitigating glacier melt caused by aerosols over the TP but is also of great significance for the protection of the ecological environment of the TP.